Association of anxiety and depression to headache, abdominal- and musculoskeletal pain in children - Nilsen, Marianne; Weider, Siri; Halse, Marte Kathrine; Fiskum, Charlotte; Wichstrøm, Lars (Frontiers in Pain Research, 2023)
The comorbidity between recurrent pain, anxiety, and depression among children is high and well documented. However, only a few studies of the predictive effect of anxiety and depression on pain have adjusted for symptoms of the other disorder when examining the respective relations to different pain locations, rendering the unique contribution from anxiety and depression undetermined. In the current investigation we explore the strength of associations between pain at different locations with symptoms of anxiety and depression in a community sample of 10-year-old children (n=703). The children were interviewed about the frequency of pain during the last three months. Parents and children were interviewed separately about symptoms of anxiety and depression using a semi-structured diagnostic interview. Results of three multivariate regression models for each of headache, abdominal and musculoskeletal pain revealed that depression was associated with musculoskeletal pain and headache, whereas anxiety was not. The associations for depression were not significantly stronger compared to anxiety. Gender-specific models found that depression was related to headache only among girls, but the association was not statistically different compared to boys. These results may, in turn, influence our interpretation of different forms of pain in children, with less weight given to abdominal symptoms viewed as a strong correlate with psychological problems, compared to for instance headache. The results provided no clear support for neither a differential relationship between anxiety and pain and depression and pain nor gender differences.